Reflections on the International Criminal Court's jurisdictional reach (2005)
Héctor Olásolo: Doctor in Law. Associate legal officer in Chambers at the International Criminal Court. Honorary Senior Lecturer in the Department of Criminal Law at the University of Utrecht. Former member of the Spanish delegation to the International Criminal Court Preparatory Commission. Former associate legal officer at the legal advisory and appeal sections of the International Criminal Tribunal for the former Yugoslavia, Office of the Prosecutor. The views expressed herein are those of the author alone and do not necessarily reflect the views of the International Criminal Court, the International Criminal Tribunal for the former Yugoslavia, the United Nations in general or the Spanish Government.